Peran Komunikasi dalam Memahami Motivasi dan Pengalaman Pengguna Judi Togel : Studi Kualitatif pada Pemain Aktif Judi Togel di Kampung Maybrat, Papua Barat Daya - Lestari, Rahmawati Sukma; Lingara, Jannah; Nadiyah, Nurfadhilah (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2023)
This research aims to analyze the influence of economic behavior on dependency on lottery gambling among the community. The aim of this research is to provide insight into how economic factors influence people's behavior in using lottery gambling. This research uses a descriptive qualitative approach using interview techniques. Gambling is an option that is considered very promising for profits without having to work hard. Gambling is considered the right choice for some people to make money in an easier way. Results of interviews with respondents obtained through interviews related to lottery gambling. Factors that influence respondents in playing lottery gambling are helping the economy, especially to meet daily needs such as paying for school or boarding. This suggests that pressing financial needs prompted him to engage in gambling practices as a way to earn extra money